Quantifying the Size of the Contraband Cell Phone Problem: insights From a Large Rural State Penitentiary - Grommon, Eric L. (The prison journal, 2018)
Cell phones are one of the most challenging forms of contraband for correctional facilities. The size of this problem is difficult to quantify. Confiscation data are only able to tell a partial story. Through the use of a unique data collection effort, this research details the number of contraband cell phones within a facility and offers the first attempt to estimate the gap that exists between the number of contraband cell phones available and the number that are confiscated. In light of the findings, implications for policy and an agenda for research on contraband cell phone market dynamics are provided.